Low-volume HIIT and MICT speed VO2 kinetics during high-intensity "work-to-work" cycling with a similar time-course in type 2 diabetes - Gildea, Norita; Egana, Mikel (My University, 2022)
We assessed the rates of adjustment in oxygen uptake (V̇o2) and muscle deoxygenation [i.e., deoxygenated hemoglobin and myoglobin, (HHb + Mb)] during the on-transition to high-intensity cycling initiated from an elevated baseline (work-to-work, w-to-w) before training and at weeks 3, 6, 9, and 12 of low-volume high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) in type 2 diabetes (T2D). Participants were randomly assigned to MICT (n = 11, 50 min of moderate-intensity cycling), HIIT (n = 8, 10 × 1 min of high-intensity cycling separated by 1 min of light cycling) or nonexercising control (n = 9) groups. Exercising groups trained three times per week. Participants completed two w-to-w transitions at each time point consisting of sequential step increments to moderate- and high-intensity work-rates. [HHb + Mb] kinetics were measured by near-infrared spectroscopy at the vastus lateralis muscle. The pretraining time constant of the primary phase of V̇o2 (V̇o2 τp) and the amplitude of the V̇o2 slow component (V̇o2 As) of the high-intensity w-to-w bout decreased (P < 0.05) by a similar magnitude at week 3 of training in both MICT (from 56 ± 9 to 43 ± 6 s, and from 0.17 ± 0.07 to 0.09 ± 0.05 L/min, respectively) and HIIT (from 56 ± 8 to 42 ± 6 s, and from 0.18 ± 0.05 to 0.09 ± 0.08 L/min, respectively) with no further changes thereafter. No changes were reported in controls. The parameter estimates of Δ[HHb + Mb] remained unchanged in all groups. MICT and HIIT elicited comparable improvements in V̇o2 kinetics without changes in muscle deoxygenation kinetics during high-intensity exercise initiated from an elevated baseline in T2D despite training volume and time commitment being ∼50% lower in the HIIT group. NEW & NOTEWORTHY Three weeks of high-intensity interval training and moderate-intensity continuous training decreased the time constant of the primary phase of oxygen uptake (V̇o2) and amplitude of the V̇o2 slow component during a high-intensity exercise initiated from an elevated baseline, a protocol that mimics the abrupt metabolic transitions akin to those in daily life, in type 2 diabetes. These V̇o2 kinetics improvements were maintained until the end of the 12-wk intervention without changes in muscle deoxygenation kinetics.
PUBLISHED
Keywords: Ageing